Organizational Culture and Job Satisfaction of Midwives in therapeutic , Teaching and Health Centers of Karaj, Iran - Mina Amiri; Hamid Alavi Majd (Golestan University of Medical Sciences, 2017)
Background: Health system is seeking to provide health services for people by creating the desirable culture and climate, in which, human resources are ready to provide the effective and high quality services. This study aimed to investigate the relationship between organizational culture and job satisfaction of midwives therapeutic, teaching and health centers of Karaj. Methods: in this cross-sectional study, 200 midwives working in selected training, health and treatment centers of Alborz University of Medical Sciences were randomly chosen. The instruments were Robbins 'self-report organizational culture questionnaire and Herzberg job satisfaction questionnaire. The data was analyzed by Friedman test and Pearson's correlation coefficient.  Results: Most midwives showed average organizational culture and job satisfaction. Pearson correlation coefficient showed a significant and direct relationship between organizational culture and job satisfaction (P>0.001 and r=0.71). Organizational identity and job status had the highest scores of organizational culture and job satisfaction, respectively. Conclusion: The results show that there is a positive correlation between organizational culture and midwives' job satisfaction. Thus, the desirable organizational culture results in job satisfaction, desirable performance and high efficiency. Organizational culture and the degree of moral stress in working place can affect job satisfaction and desertion  ; therefore, making every effort to improve the organizational culture can increase the efficiency of the employees.